Feed intake of selected vegetables and fruits by coconut lorikeet (Trichoglossus haematodus) in a colony system (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prijono SN,Rachmatika R, Maharani S. 2021. Feed intake of selected vegetables and fruits by coconut lorikeet (Trichoglossus haematodus) in a colony system. Biodiversitas 22: 4818-4828. Coconut lorikeet (Trichoglossus haematodus (Linnaeus 1771)) is nectarivorous bird. An imbalanced diet is a common problem with lorikeet were kept in captivity. The research method was completely randomized design arranged in a factorial with two factors. The first factor consisted of five types of vegetables or five types of fruits while the second factor consisted of five height levels of feed cup placement (30 cm, 60 cm, 90 cm, 120 cm and, 150 cm from the roof). This  study aimed to get information on the feed intake of selected vegetables and fruits that have high attractiveness to meet nutrient requirements and balanced diet for coconut lorikeets kept in a colony aviary. The feed intake of vegetable soybean (26.68 g) was higher than yardlong bean (21.63 g), green cabbage (19.12 g), red cabbage (16.24 g), and broccoli (14.27 g), while the feed intake of plum (14.15 g) was higher than apple (12.31 g), pomegranate (10.88 g), papaya (10.55 g) and guava (9.82 g). Vegetable and fruit intake by six coconut lorikeets in a colony system were 20.80% of the daily diet, and the siwalan sugar solution was 79.20% of the daily diet. It was suggested that the coconut lorikeets should be fed more vegetables than fruits. A good quality, varied and balanced diet will make the coconut lorikeets healthy and it will support future conservation effort.
Keywords: captivity; feed intake; fruit; lorikeet; vegetable